Descartes and the laws of charity. Public and private law in the ’Letter to Voetius’ - Pavesi, Pablo (Revista de Filosofía, 2019)
We pose this problem: Descartes responds to Voetius’ irrational accusation by resorting once, on his own initiative, to Gospel, an interpretation that reviews the laws of charity as akin to the laws of natural friendship governing pastor and teacher roles. We propose that the Letter be a legal argument. Descartes has no interest in theological virtues: facing irrationality, he delves into private law to prove that Voetius is not a true teacher, or a true pastor, and encroaches on the function of judge.